1999
DOI: 10.1038/11109
|View full text |Cite
|
Sign up to set email alerts
|

A new internal-ribosome-entry-site motif potentiates XIAP- mediated cytoprotection

Abstract: rogrammed cell death (apoptosis) plays a critical part in regulating cell turnover during embryogenesis, metamorphosis, tissue homeostasis and viral infection 1 . Dysregulation of apoptosis occurs in such pathologies as cancer, autoimmunity, immunodeficiency and neurodegeneration. Proteins of the inhibitor-ofapoptosis (IAP) family are intrinsic cellular suppressors of apoptosis and are represented by highly conserved members found from insect viruses to mammals 2-4 . The most potent mammalian IAP is the X-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
329
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(345 citation statements)
references
References 9 publications
14
329
0
2
Order By: Relevance
“…As certain types of cell stress pathways are known to influence mechanisms that control mRNA translation, and as p53 function is reliant on its capacity to rapidly respond to cell stress, it is not surprising that p53 mRNA translation is responsive to cell stress. For example, the expression of apoptosis linked APAF-1 (Coldwell et al, 2000), X-linked inhibitor of apoptosis protein (Holcik et al, 1999) as well as the hypoxia response factor hypoxia-inducible factor-a are regulated through IRESs (Lang et al, 2002). Hence, the capacity of the p53 mRNA to coordinate the synthesis of p53 products with the synthesis of executing stress-response factors could form an important part in the p53 response to changes in the cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…As certain types of cell stress pathways are known to influence mechanisms that control mRNA translation, and as p53 function is reliant on its capacity to rapidly respond to cell stress, it is not surprising that p53 mRNA translation is responsive to cell stress. For example, the expression of apoptosis linked APAF-1 (Coldwell et al, 2000), X-linked inhibitor of apoptosis protein (Holcik et al, 1999) as well as the hypoxia response factor hypoxia-inducible factor-a are regulated through IRESs (Lang et al, 2002). Hence, the capacity of the p53 mRNA to coordinate the synthesis of p53 products with the synthesis of executing stress-response factors could form an important part in the p53 response to changes in the cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is mediated by structured regions of RNA termed internal ribosome entry segments (IRES), and these have the ability to direct ribosome binding some considerable distance (up to 1000 nts) from the 5' end of the message. IRESs were originally discovered in picornaviral mRNAs, but have now been identi®ed in a number of eukaryotic mRNAs, the protein products of which are involved in the control of cell growth including, FGF-2 (Vagner et al, 1995), VEGF (Miller et al, 1998;Stein et al, 1998), PDGF (Bernstein et al, 1997) and c-myc (Nanbru et al, 1997;Stoneley et al, 1998) and cell death Holcik et al, 1999). In the case of c-myc we have shown that initiation of protein synthesis can occur by two distinct mechanisms; cap-dependent scanning and IRES mediated .…”
mentioning
confidence: 96%
“…29 Serum starvation of mammalian cell cultures showed induction of Bcl-2 IRES 30 and activated translation of XIAP mRNA. 31 IRES-mediated translation of p27 Kip1 mRNA contributes to maintenance of G1 phase of the cell cycle and the expression of p27 Kip1 was found to be iron sensitive. 32,33 These studies reveal a novel aspect of activation of IRESmediated translation of eukaryotic mRNAs due to nutrient shortage, resulting in the synthesis of proteins essential for cell survival or apoptosis.…”
mentioning
confidence: 98%